2020
DOI: 10.31933/dijemss.v1i6.470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organizational Commitment, Work Satisfaction, Work Motivation Toward Organizational Citizenship Behavior

Abstract: The purpose of this study was to measure the effect of organizational commitment, job satisfaction and work motivation on organizational citizenship behavior in SMK Satria Srengseng teachers, this research is quantitative. The population is all teaching teachers and staff. The technique in taking samples uses nonrandom sampling in the form of saturated samples with a total of 70 teachers. Data obtained from the results of the study were analyzed using multiple linear regression. T-test results for the variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…Previous studies that have been conducted by Iswiarto & Soliha (2019); Muchtadin & Chaerudin (2020); Widarko & Anwarodin (2022) Shows a significant effect of work motivation on organizational citizenship behavior in a positive direction, but the findings in the study conducted by Hamzah et al, (2022) There was no significant effect of work motivation on organizational citizenship behavior. The inconsistency of the results of the study prompted researchers to re-study the effect of work motivation on organizational citizenship behavior by including job satisfaction as a mediation variable, which aims to bridge the research gap that occurs.…”
Section: Introductionmentioning
confidence: 61%
“…Previous studies that have been conducted by Iswiarto & Soliha (2019); Muchtadin & Chaerudin (2020); Widarko & Anwarodin (2022) Shows a significant effect of work motivation on organizational citizenship behavior in a positive direction, but the findings in the study conducted by Hamzah et al, (2022) There was no significant effect of work motivation on organizational citizenship behavior. The inconsistency of the results of the study prompted researchers to re-study the effect of work motivation on organizational citizenship behavior by including job satisfaction as a mediation variable, which aims to bridge the research gap that occurs.…”
Section: Introductionmentioning
confidence: 61%
“…The results of the F test are shown in table 5 with a p value < 0.001, so it can be said that psychological capital and affective commitment simultaneously influence organizational citizenship behavior. Previous research found a joint influence of organizational commitment, job satisfaction, and work motivation on OCB [22].…”
Section: F Testmentioning
confidence: 89%
“…This research involves four variables namely: work motivation, organizational climate, organizational commitment, and One factor affecting OCB is work motivation. Research done by Shaaban (2018), Muchtadin and Chaerudin (2020), Sukarman et al (2018) and Margahana et al (2018) show that work motivation has a positive and significant influence toward OCB. However, research with different result was done by Haryati (2019) which shows that motivation is not positively and significantly affecting OCB.…”
Section: Methodsmentioning
confidence: 99%